2017
DOI: 10.1177/0954405417703428
|View full text |Cite
|
Sign up to set email alerts
|

The use of high-frequency acoustic emission analysis for in-process assessment of the surface quality of aluminium alloy 5251 in abrasive waterjet machining

Abstract: In this article, the use of acoustic emission signal analysis for in-process assessment of the surface quality in abrasive waterjet machining is presented. The authors carried out an analysis of the influence of the cutting head traverse speed (considered in this case as the performance measurement) on the flatness, waviness and roughness of surfaces made of aluminium alloy 5251 after cutting process, as well as the influence of changing the quality factor on values of selected descriptors of the emitted high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…Sutowski et al presented a possible diagnostic method to be applied in the abrasive waterjet machining [28]. The authors confirmed the clear influence of machining conditions on the geometric structure of the obtained cuts and the registered values of the emitted high-frequency stress waves.…”
Section: Acoustic Emissionmentioning
confidence: 81%
“…Sutowski et al presented a possible diagnostic method to be applied in the abrasive waterjet machining [28]. The authors confirmed the clear influence of machining conditions on the geometric structure of the obtained cuts and the registered values of the emitted high-frequency stress waves.…”
Section: Acoustic Emissionmentioning
confidence: 81%
“…According to this approach, the concentration density of abrasive impact stress at a given meshed area of boundary surface can be denoted as an unlabeled data { I d [ ( x k , y k ) ; μ , σ 2 ] } x k = 1 , y k = 1 M k , N k , where I d [ false( x k , y k false) ; μ , σ 2 ] M k × N k . The encoder of NSAE uses a mapping function G to determine the concentration density of impact stress as 27,28…”
Section: Nsae-anfismentioning
confidence: 99%
“…The encoder of NSAE uses a mapping function G to determine the concentration density of impact stress as 27,28…”
Section: Nsae-anfismentioning
confidence: 99%
“…Under normal conditions, this value is lower, which means that the method of machining materials being discussed may be considered as relatively accurate. Given the above, AWJ, which is a universal technological tool, provides itself with a wider range of machining applications, enabling the shaping of many types of materials, such as metals and its alloys [ 14 , 15 , 16 , 17 , 18 , 19 ], ceramic, glass [ 20 ], composites [ 21 , 22 ], flammable materials, leather, and natural stone-based materials [ 23 ], as well as regenerating the cutting ability of grinding tools [ 24 ]. Nevertheless, there is still a need for further research related to this technology in order to increase the efficiency of material machining.…”
Section: Introductionmentioning
confidence: 99%